1974
DOI: 10.1001/archneur.1974.00490410073008
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocorticotrophic and Growth Hormone Secretion

Abstract: The effect of pneumoencephalography on plasma and cerebrospinal fluid (CSF) adrenocorticotrophic (ACTH) and growth hormone concentrations was studied in patients with and without hypothalamicpituitary disorders. In those without hypothalamic-pituitary disease, basal plasma and CSF ACTH levels were approximately equal, whereas plasma growth hormone levels were higher than CSF levels. Associated with the stress of the procedure, both ACTH and growth hormone concentrations increased in the plasma without a corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1980
1980
1985
1985

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…Kleerekoperet al [34] reported ACTH serum concentrations of 0-85 pg/ml with CSF concentrations of 25-75 pg/ml. In a larger series of patients without endocrine disease studied with simultaneous sampling at pneumoencephalography, a mean ACTH concentration of approximately 75 pg/ml in serum and 100 pg/ml in CSF was reported [2], Similar re sults were reported by Kendall et al [32,33].…”
Section: Prolactinsupporting
confidence: 82%
See 2 more Smart Citations
“…Kleerekoperet al [34] reported ACTH serum concentrations of 0-85 pg/ml with CSF concentrations of 25-75 pg/ml. In a larger series of patients without endocrine disease studied with simultaneous sampling at pneumoencephalography, a mean ACTH concentration of approximately 75 pg/ml in serum and 100 pg/ml in CSF was reported [2], Similar re sults were reported by Kendall et al [32,33].…”
Section: Prolactinsupporting
confidence: 82%
“…The serum and CSF levels of GH in three acromegalics with suspected su prasellar tumor extension were considerably higher and the serum CSF ratio lower. Several subsequent studies have supported the inferences from this work that (a) the serum CSF-GH ratio is relatively high, (b) that CSF as well as se rum GH is increased in acromegaly, and (c) that CSF GH is especially elevated in the acromegalic patient with suprasel lar extention of the tumor [2,30,55]. However, there have been reports that CSF GH can be increased in the acrome galic without suprasellar extension [50], Additionally, in ac romegaly with suprasellar extension, an increased CSF can occur without a proportionately increased serum GH [32] and even with a higher CSF than serum GH [24,50], As with other hormones when there is suprasellar exten sion of pituitary tumors, the presence of relatively high lev els of GH in the CSF of such patients suggests direct secre tion from the tumor into the surrounding CSF [30], This may even occur under normal conditions by retrogarde transport of GH from the pituitary to the CSF [6], This view is supported by the comparable CSF to serum ratio of GFi and structurally similar PRL and by the lower CSF serum ratio of chorionic somatomammatropin, also structurally similar to GH but, unlike PRL, of placental origin [5],…”
Section: Growth Hormonesupporting
confidence: 74%
See 1 more Smart Citation
“…Under differ ent circumstances, Nakao et al [26], Hosobuchi [13], and Allen et al [2,3] have found no significant relationship be tween plasma and CSF ACTH and p-E concentrations over time in humans. In contrast, Basso et al [4] found parallel increases in plasma and CSF P-E concentrations after ad ministering ceruletide to humans.…”
Section: Discussionmentioning
confidence: 99%